GAYA HIDUP MODERN PEREMPUAN MINANGKABAU AWAL ABAD KE-20 - Febri Angraini (PERADA, 2021)
This paper contains a general description of modernity in the lives of Minangkabau women in the early 20th century. The years 1900 to 1942 were a general description of modernity in the life of the intended woman. The Dutch East Indies government has brought the Western style of thinking through education. Ethical Politics facilitates the way of modernization to open up and change the lifestyle of Minangkabau women. The process of criticism as an effort to leave the conventional lifestyle was brought by Minangkabau women who contributed in the world of education. They seek changes in conventional custom systems. Modern lifestyle behavior then occurs in the daily life of Minangkabau women. Modernity in Minangkabau is a combination of traditional, Islamic, and western values affecting various aspects in Minangkabau society. The impact on modernity in Minangkabau, from a positive aspect, is to bring a breakthrough in education for women, while the negative impact is the dispute of the elderly and young people and the emergence of habits following the trends.